Protective role of 3-mercaptopyruvate sulfurtransferase (MPST) in the development of metabolic syndrome and vascular inflammation - Paraskevas Zampas; Zhen Li; Antonia Katsouda; Aimilia Varela; Stelios Psarras; Constantinos H. Davos; David J. Lefer; Andreas Papapetropoulos (Pharmacological Research)
Metabolic syndrome (MetS) is a cluster of metabolic abnormalities that occur concurrently and increase the risk of cardiovascular disease. 3-mercaptopyruvate sulfurtransferase (MPST) is a cysteine-catabolizing enzyme that yields pyruvate and hydrogen sulfide (H2S) and plays a central role in the regulation of energy homeostasis. Herein, we seek to investigate the role of MPST/H2S in MetS and its cardiovascular consequences using a mouse model of the disease. Mice were fed a high-fat diet (HFD) for 15 weeks to induce obesity and hyperglycemia and administrated a nitric oxide synthase inhibitor, during the last 5 weeks to induce hypertension and MetS. This model caused a mild left ventricular (LV) diastolic dysfunction and vascular endothelial dysfunction. Free H2S and sulfane-sulfur levels were decreased in the aorta, but unaltered in the heart. Also, downregulation of MPST and thiosulfate sulfuretransferase (TST) were observed in the aorta. Global deletion of Mpst (Mpst-/-) resulted in increased body weight and greater glucose intolerance in mice with MetS, without affecting their blood pressure, and caused an upregulation of genes involved in immune responses in the vasculature suggestive of T-cell infiltration and activation. Pharmacological restoration of H2S levels ameliorated the comorbidities of MetS; GYY4137 administration reduced body weight and blood pressure, attenuated cardiac fibrosis and improved glucose handling and endothelium-dependent relaxation. In conclusion, this study found that reduced MPST/H2S exacerbates the pathological changes associated with MetS and contributes to vascular inflammation. H2S supplementation emerges as a potential therapeutic approach to treat the abnormalities associated with MetS.